Albuminuria: pathophysiology, epidemiology and clinical relevance of an emerging marker for cardiovascular disease. (September 2007) - Thoenes, Martin; Bramlage, Peter; Khan, Bobby V; Schieffer, Bernhard; Kirch, Wilhelm; Weir, Matthew R
Albuminuria has emerged from being a sign of early kidney disease in diabetes to an independent predictor of cardiovascular risk. Epidemiological studies suggest that microalbuminuria (30––300  mg/d) is present in 5––19% of the general population, in up to 23% of patients with hypertenstion and in up to 40% of patients with diabetes. Recent data suggest an even higher prevalence in certain patient populations. As it is associated with a variety of important cardiovascular risk factors, including prediabetes, dyslipidemia and the metabolic syndrome, detection of albumin in the urine represents an important diagnostic window for systemic micro- or macrovascular damage. Various studies have demonstrated the predictive value of all levels of albuminuria for future cardiovascular events in patients with diabetes, hypertension or overt cardiovascular disease, as well as in the general population. Annual screening for microalbuminuria is now recommended by international diabetes guidelines for patients with diabetes, and may be appropriate for nondiabetics with risk factors for cardiovascular disease.